ASSESSING THE POTENTIAL OF WEATHER FISHERMEN'S FIELD SCHOOL TO SUPPORT BLUE ECONOMY IN INDONESIA - Dewita, Anggi (Jurnal Widya Climago, 2024)
The blue economy represents an innovative approach to harnessing the marine economy's potential while safeguarding the sea and its ecosystems. This paper aims to explore the potential contribution of Indonesia's Meteorological, Climatological, and Geophysical Agency (BMKG) through Fishermen's Weather Field Schools (SLCN) in supporting the country's blue economy. By analyzing the role of SLCN as a collaborative platform for stakeholders in the fisheries industry, the paper seeks to integrate stakeholder capabilities into a comprehensive framework for a successful and sustainable blue economy. It recommends leveraging SLCN as a ready-to-use platform for stakeholder interaction and encourages collaboration among researchers, government agencies, and non-governmental organizations to ensure the safety and success of local fishermen through effective research and communication.